National Health Insurance Data as a Research Tool in Korean Medicine: a guide to database utilization and methodological approaches - Chan-Young Kwon; Il-Su Park (Journal of Pharmacopuncture)
Objectives: This study aims to provide a practical framework for Korean medicine (KM) researchers on effectively utilizing Korean National Health Insurance (NHI) data, focusing on database characteristics, access methods, and methodological considerations for generating high-quality evidence in KM research. Methods: This study analyzed the NHI data system structure, analyzing its two major databases: the National Health Insurance Service (NHIS) and Health Insurance Review and Assessment Service (HIRA). We examined available data types, access protocols, and methodological approaches, with particular emphasis on their application in KM research. The study synthesized current challenges and opportunities specific to KM research using these databases. Result: Our analysis revealed three key findings: 1) The distinct characteristics and complementary nature of NHIS and HIRA databases, with NHIS providing comprehensive longitudinal data suitable for cohort studies and HIRA offering detailed cross-sectional data optimal for utilization pattern analysis; 2) Multiple data access options including Sample Research DB and Customized Research DB from NHIS, and Patient Sample Data and Customized Research Data from HIRA, each with specific advantages for different research designs; 3) Critical methodological considerations for KM research, particularly addressing the limited coverage of KM services (0.8% of total covered items) and the high proportion of non-covered services in KM practices (24.2-49.2% across different institution types). Conclusion: For effective utilization of NHI data in KM research, we recommend: 1) Implementing hybrid research designs that combine health insurance data with institutional data to overcome limited KM coverage; 2) Establishing clear operational definitions and applying appropriate statistical methods for bias adjustment; 3) Working toward developing a specialized Korean Medicine Utilization Cohort Database. These approaches can enhance the quality and generalizability of KM research using health insurance data, ultimately contributing to evidence-based practice in Korean medicine.